Stridor in an 11-year-old child. (10th December 2013) - Abraham, Deepu; Karuvattil, Rajesh; Fitzpatrick, Maggie
Abstract : Stridor in older children can be due to diverse aetiology that includes infections, anaphylaxis and rarely systemic conditions leading to hypocalcaemia. We report the case of a previously asymptomatic 11-year-old girl who presented to the casualty with stridor due to hypocalcaemia. The aetiological investigations for hypocalcaemia uncovered previously undetected chronic renal failure, possibly due to a rare autosomal recessive condition called nephronophthisis. We report this case to highlight the importance of widening the diagnostic focus for children presenting with stridor, especially when they fall outside the usual age group for infections like croup, or when the history is atypical.